EatxCali Keynote speaker: Barry Popkin, University of North Carolina, USA. The nutritional triple burden: Latin America’s heavyweight champions - International Center for Tropical Agriculture (2015)
Keynote speaker: Barry Popkin, University of North Carolina, USA. EATxCali brings together representatives from academic and government institutions, international agencies, businesses, and civil society to rebuild food systems, and ensure that consumers have access to healthy and more sustainably produced food.